Psychology Politics Resistance: Position Statement - Britain, PPR (PINS-Psychology in Society, 2026)
Psychology Politics Resistance is a network of people - both psychologists and non-psychologists - who are prepared to oppose the abusive uses of psychology. This means challenging the ideas within psychology that lead to oppressive practices, supporting those who are on the receiving end, and using psychological knowledge positively to help those engaged in struggles for social justice.